Perancangan Eco-Park Mangrove di Taman Hutan Raya Ngurah Rai: Bahasa Indonesia - I Gusti Ngurah Made Dharma Suputra; Gde Bagus Andhika Wicaksana; Agus Kurniawan; Ni Wayan Nurwarsih; Tjokorda Gede Dalem Suparsa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Bali has a mangrove forest with an area of 1,353 ha, which has been designated as a Grand Forest Park since 1993. The economic and environmental potential of this mangrove includes natural recreation, processed products, and ecosystem sustainability. Irresponsible use can damage ecosystems, affect sustainability, and threaten ecotourism. An ecotourism concept that pays attention to ecological sustainability is proposed as a solution, with the application of renewable materials such as bamboo and wood in the planning and design of tourist facilities. This approach aims to minimize damage to the mangrove ecosystem. The design of the Mangrove Ecopark in Tahura Ngurah Rai is expected to improve the local community's economy and support the development of sustainable natural tourism destinations in Bali.